(untitled) (SETARA : Jurnal Ilmu Hukum, 2024)
The selection of Supreme Court Justices often attracts public attention because it concerns the integrity and independence of the judiciary. This study examines the regulation of Supreme Court Justice nominations in the Indonesian legal system and formulates the ideal authority of the Judicial Commission in selecting and approving candidates with integrity. This research uses a normative juridical method with statutory, conceptual, and historical approaches. The legal materials consist of primary and secondary legal materials. The study finds that potential conflicts of interest arising from the involvement of the House of Representatives in fit and proper tests are not fully consistent with the principle of separation of powers under the 1945 Constitution. An ideal selection process should focus on integrity, professionalism, and transparency without political intervention. The establishment of an independent and credible National Selection Committee can support a more transparent and accountable selection process.